The Effect Of Problem-Based Learning Model On The Creative Thinking Ability Of Physics Students Of Class XI Of Sma Negeri 10 Makassar - Anita Wulandari*; Hasyim, Mutahharah; Usman (Journal of Physics Education : Review and Research, 2025)
This study aims to determine the effect of problem-based learning on the creative thinking skills of 11th-grade students at SMA Negeri 10 Makassar in physics lessons. The research method used is quantitative with a posttest-only control design. The research sample consisted of 28 students divided into two groups: one taught using problem-based learning and the other using a conventional model. The instrument used was an essay test on creative thinking skills, validated using the Gregory test. The results showed that students taught with problem-based learning had an average score of 32.14, while those taught with the conventional model had an average score of 31.00. Inferential analysis showed no significant difference in creative thinking skills between students taught using problem-based learning and those taught using the conventional model. However, problem-based learning still encourages students to actively engage in learning and helps them develop creative thinking skills, which are essential for solving various physics problems in everyday life.